Determinants of access to insecticide-treated nets in Sub-Saharan Africa: A multilevel cross-country analysis using 29 DHS data - Jember Azanaw; Eshetu Abera Worede (PLoS ONE, 2025)
Background Having access to Insecticide-Treated Nets (ITNs) is crucial for avoiding malaria in Sub-Saharan Africa (SSA), where the disease burden is disproportionately high. Despite their efficacy, socioeconomic, demographic, and geographic factors continue to cause notable differences in ITN access within and between nations. By employing a multilevel analysis of data from 29 Demographic and Health Surveys (DHS) throughout SSA, this study seeks to fill knowledge gaps about the factors that influence access at the individual and community levels. Methods The study utilized data from 29 DHS surveys in SSA, which encompassed 214,181 households. Factors affecting access to ITN at the individual and community levels were examined using multilevel logistic regression models. Household head characteristics (sex, marital status, education, wealth index, television access, and family size) were among the individual-level factors. On the other hand, community-level characteristics included geography, kind of home, poverty, media exposure, and education. The Akaike Information Criterion (AIC), Bayesian Information Criterion (BIC), and deviance were used to evaluate the model’s fitness. Measures of variation, including the Median Odds Ratio (MOR), Proportional Change in Variance (PCV), and Intraclass Correlation Coefficient (ICC), were used to assess the effects at the community level. Results ITNs were reported by just 32.11% of households, with notable differences across socioeconomic classes and geographical areas. Higher ITN access was substantially correlated with married household heads, wealthier families, larger family sizes, and higher educational attainment. Access was also greatly enhanced by community-level factors such as urban residency, media exposure, and higher education. The best fit was Model 3, which explained 15.24% of the variance in ITN access by combining characteristics at the person and community levels. There were clear regional differences, with West Africa having higher probabilities of access than East Africa (AOR = 4.48). Conclusion The study highlights the multifaceted determinants of ITN access in SSA, emphasizing the need for targeted interventions addressing both individual and community-level barriers. Strengthening distribution networks, increasing funding for subsidized ITN programs and enhancing public health education is essential for achieving universal coverage and reducing the malaria burden in the region.